2012
DOI: 10.1245/s10434-012-2772-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Either Estrogen or Progesterone Receptor Expression Is Associated with Poor Survival Outcome among Luminal A Breast Cancer Subtype

Abstract: Current results suggest that the luminal A subtype is also heterogeneous and each subgroup has unique clinicopathologic characteristics. Lack of either ER or PR expression is associated with worse survival, especially among node-positive luminal A subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
(40 reference statements)
3
32
0
Order By: Relevance
“…The initial search strategy identified 3900 articles, of which 51 full articles were deemed eligible for review. After application of inclusion and exclusion criteria, eight studies were selected for inclusion ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search strategy identified 3900 articles, of which 51 full articles were deemed eligible for review. After application of inclusion and exclusion criteria, eight studies were selected for inclusion ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Clinicopathological characteristics, including T category, HER2 status, grade, nodal positivity and Ki‐67 index results are summarized in Table . Six of the eight studies reported mean age for both groups; the mean age in the ER+PgR– and ER+PgR+ groups was 53·1 (range 46–58) and 49·6 (range 46–48) years respectively ( Table S1 , supporting information). Four studies reported on the menopausal status of patients at diagnosis; 3497 of 5363 (65·2 per cent) were premenopausal in the ER+PgR+ group compared with 282 of 776 (36·3 per cent) in the ER+PgR– group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it seems that molecular subtypes might be divided into additional subgroups with further data from transcriptomic analyses. For example, the lack of ESR1 or PGR receptors in luminal A subtype can define new subgroups with unique clinicopathologic characteristics [25]. Further molecular markers are capable to estimate prognosis in a subtype-independent manner using claudin expression [26].…”
Section: The Discovery Of Molecular Subtypesmentioning
confidence: 99%
“…After binding to their respective intracellular receptors [Estrogen Receptor (ER) and Progesterone Receptor (PR)] both these hormones activate a set of signalling events that ultimately result in enhancing the cellular proliferation rate of normal breast epithelium 4 . ER−/PR− breast tumors are shown to have a poor prognosis compared to ER+/PR+ tumors 5 . Similarly, human epidermal growth factor (Her2neu) status is one of the other determinants of the rate of breast tumor proliferation, with Her2neu+ tumors representing a more aggressive form 6 .…”
Section: Introductionmentioning
confidence: 99%